Perdebatan Teoritis Terhadap Perluasan Ruang Lingkup Keuangan Negara Di Indonesia - Sorik, Sutan; Dwiatmoko, Anang (Jurnal Hukum & Pembangunan, 2022)
The focus of this research is the expansion of the scope of state finance which currently still presents cross-thinking. The existence of a coherent understanding regarding the application of the financial legal status of a legal entity, whether it is related to state finances, regional finances, state-owned enterprises (BUMN) finances, regional-owned enterprises (BUMD) finances, or private finances is the background why this happens. In the development of the expansion of the scope of state finances, it became even stronger when the Constitutional Court also issued several decisions in response to requests for judicial review, starting from the Decision of the Constitutional Court Number 77/PUU-IX/2011, Decision of the Constitutional Court Number 48/PUU-IX/2013, and Constitutional Court Decision Number 62/PUU-IX/2013. The elasticity of state finances with the concept through a narrow area and also a broad spectrum for the status of state finances will depend on how the parties interpret and use the meaning of state finances themselves. The opening of a broad interpretation of state finances is not only a matter of audit authority but also a problem that is increasingly widespread. The type of research used is normative juridical research. The research method is qualitative. The results of the study found that there was no unified opinion regarding state finances, whether based on theory, laws and regulations, or the decision of the Constitutional Court.